Influência da utilização do extrato hidroalcoólico de própolis sobre o desenvolvimento de fungos e características físicoquímicas e sensoriais do salame tipo italiano. - Lappe, Rosiele (2004)
The objective of the present work evaluate the efficiency of the hydro alcoholic extract of propolis in different concentrations in the control from the development of moulds in the Italian dry cured sausage surface, as well as to its influence about the parameters physic-chemical and sensory. The solution of propolis was diluted in four different concentrations: 0,5; 1; 2 and 4%. The salami was manufactured and divided in five lots, being four handlings in the respective concentrations and a control. The treatments were carried through spray from the solution of propolis on the salamis. The effect of the solution of propolis about the physic-chemical characteristics and on the development of moulds was evaluated on the 1º, 7º, 14º and 19º day when it was finished the production of the salami. The evaluation of the sensorial characteristics, counts of Staphylococcus coagulase positive, total coliforms and coliforms at 45°C were carried out almost in the end of the trial. Counts of moulds and yeasts did not present significant statistical difference. However, the difference of logarithmic cycles between the lot control and the treatments was considered sufficient under the microbiological point of view. In the lot control, the growth of moulds were well more pronounced so much in number of colonies as regards the kind of coloring, which in those products presented dark coloring to the greenish one. In the treated salamis the desirable, white growth of moulds in that kind of product occurred barely. The pH of the treated salamis had a light increase in the end of the ripening, the too characteristics physical chemistry of the salamis did not differ significantly by the use from the solution of propolis. The sensory attributes analyzed showed that the treated salamis with different concentrations of propolis and the group control result in a product with sensory characteristics similar, only the attribute texture revealed a preference of the tasters by the treated samples with 2 and 4% of propolis. Not presence occurred of coliforms at 45°C and the counts of Staphylococcus coagulase positive and total coliforms they found themselves inside the limits permitted by the legislation in force for the Italian salami kind. Therefore, I concluded that the usage of hydro alcoholic solution of propolis was efficient in the control of moulds formation, mainly in the concentrations of 2 and 4% and, in a general form, did not influence significantly in the characteristics physical chemistry and sensory of the Italian salami kind.